Philip Roth. - Brauner, David (Manchester University Press, 2007)
This is a groundbreaking study of the most important contemporary American novelist, Philip Roth. Reading the author alongside a number of his contemporaries, and focusing particularly on his later fiction, this book offers a highly accessible, informative and persuasive view of Roth as an intellectually adventurous and stylistically brilliant writer who constantly reinvents himself in surprising ways. At the heart of this book are a number of detailed and nuanced readings of Roth?s works both in terms of their relationships with each other and with fiction by Nathaniel Hawthorne, Thomas Pynch.
Keywords: Roth, Philip -- Criticism and interpretation.; Roth, Philip; American fiction -- 20th century -- History and criticism.; Roman américain -- 20e siècle -- Histoire et critique.; LITERARY CRITICISM -- American -- General.; LITERARY CRITICISM -- General.; American fiction; English.; Languages & Literatures.; American Literature.; 1900-1999; Criticism, interpretation, etc.